THE IMPACT OF RISK MANAGEMENT ON THE PERFORMANCE OF CONSTRUCTION PROJECTS - Alshehhi, Hamad Saleh Mofleh (PEOPLE: International Journal of Social Sciences, 2024)
This research navigates the intricate landscape of the risk management in the construction industry. This paper also illuminates its profound influence on the success of the project. Diverse risk mitigation strategies have been investigated based on the impact of the same in the critical project metrics, such as adherence schedule, quality benchmark, and control of the cist; all this combined forms the foundation of this research. The objective of this research revolves around evaluating the correlation of the project's outcomes with the identification of risk. This quantifies the mitigation strategies' measurable impacts and compares their effectiveness in the stakeholders' satisfaction and the budget's control. With the empirical insights, this study aims to address the critical gap in understanding the direct link of risk management with the project's success. It equips the industry professional with evidence-based approaches to optimize risk practices, fostering resource allocation and resilience. The comparative analysis of risk management approaches empowers informed and appropriate decision-making. This reduces the disruption of and enhances financial outcomes. These findings signify a paradigm shift in project management in construction, advocating for a culture of effective and proactive risk management. It can revolutionize industry practices, increase predictability, and elevate the project's success. Implementing recommended strategies, inculcating adaptability cultivation, clear communication, and theoretical framework, and embracing complexity promises to enhance risk management effectively, guiding the instruction industry toward continuous improvement and innovation